2019
DOI: 10.1016/j.asjsur.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

‘Mesh hiatal hernioplasty’ versus ‘suture cruroplasty’ in laparoscopic para-oesophageal hernia surgery; a systematic review and meta-analysis

Abstract: In laparoscopic 'paraoesophageal hernia' (POH) repair, non-absorbable suture materials have been used to close the crural defects. More recently, various types of prosthetic mesh have been utilized to repair the defect. We conducted a systematic review with meta-analysis of the recent and up to-date studies incorporating 942 POH repairs. We examined the rates of recurrence, reoperation, and complication rates alongside operative time of these two techniques in the management POH. Randomized controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 17 publications
1
30
1
9
Order By: Relevance
“…Prior studies have demonstrated decreased recurrence rates of PEH with the use of mesh. 23 As the NSQIP does not provide a long-term follow-up, recurrence rates with the utilization of mesh were unable to be evaluated or analyzed in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have demonstrated decreased recurrence rates of PEH with the use of mesh. 23 As the NSQIP does not provide a long-term follow-up, recurrence rates with the utilization of mesh were unable to be evaluated or analyzed in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…The advantage of mesh reinforcement of cruroplasty during HH repairs remains a controversial subject in the literature due to the lack of consensus definitions of outcomes such as recurrence and complication. Several recent meta-analyses and literature reviews have varying results, with some finding no difference in outcomes (reoperation and complication rates) comparing mesh to suture reinforcement 9,20,21 , but also finding a significant reduction in hernia recurrence with the use of mesh 20,22,23 . Furthermore, studies have also compared the efficacy of biologic versus synthetic mesh.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses described a significant reduction in the recurrence rate at medium-term follow-up, including a lower risk of surgical revision, with the use of prosthetic materials, but the quality of analyzed data was poor and therefore the results are of limited level of evidence [44,45] . For instance, Tam et al [46] performed in 2016 a systematic review and meta-analysis of studies assessing the comparison between primary repair and the use of synthetic mesh.…”
Section: Peh Sac Excisionmentioning
confidence: 99%